PENGEMBANGAN PAKET SOAL MODEL PISA KONTEN CHANGE AND RELATIONSHIP UNTUK MENGUKUR KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS SISWA - Putri, Inge Wiliandani Setya (Department of Mathematics Education , University of Jember, 2017)
Abstract: PISA performance becames one of important eduacation indicator in a country. Indonesia has decided to join PISA since 2000. However the Indonesian PISA result is not surprising enough. Even, in 2012, Indonesian score in PISA lies at the lowest rank, namely 64 out 65 observed country. One of major factor is the teacher knowledge shortages of solving PISA test as well as most of teachers do not know how to develop a PISA-like test. In this paper, we try to develop a PISA-like test and implement it in a small group of students to assess their mathematical reasoning and communication ability. The result show that, from 26 respondents involved in this research, two students achieves on four level, four students achieve on three level, thirteen students achieve on two level, and seven students achieve on one level. Keywords: Pisa-like math test of change and relationship content, the students’ ability of mathematical reasoning and communication.